Disorganized attachment and defense: exploring John Bowlby's unpublished reflections. Issue 2 (4th March 2018) - Reisz, Samantha; Duschinsky, Robbie; Siegel, Daniel J
ABSTRACT: Main and Solomon were the first to create a formal infant Strange Situation classification of attachment disorganization. Bowlby's reflections on the underlying psychological processes of such behaviors, however, began early in his career, including the term "disorganization." Most of these remained unpublished but are available through the John Bowlby Archive. Bowlby saw affective experiences as the source of the attachment behavioral system's organization and regulation, and he introduced the term "effector equipment" to describe the emergent organization of attention, expectation, affect, and behavior to orchestrate responses to the environment. In his thinking, disorganization results from threat conflict, safe haven ambiguity, and/or activation without assuagement, which interfere with coordination and integration across a behavioral system. Bowlby's unpublished writings also amplify his published work on segregated systems and defensive exclusion. Bowlby's insights are relevant today and can provide greater background and clarity to current work, as researchers and clinicians consider the origins, manifestations, and meaning of disorganization.